2019
DOI: 10.1186/s12889-019-8089-y
|View full text |Cite
|
Sign up to set email alerts
|

Equity in distribution of public subsidy for noncommunicable diseases among the elderly in India: an application of benefit incidence analysis

Abstract: BackgroundRapid ageing of the population and increasing non-communicable diseases (NCDs) among the elderly is one of the major public health challenges in India. To achieve the Universal Health Coverage, ever-growing elderly population should have access to needed healthcare, and they should not face any affordability related challenge. As most of the elderly suffers from NCDs and achieving health-equity is a priority, this paper aims to - study the utilization pattern of healthcare services for treatment of N… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 36 publications
1
20
0
1
Order By: Relevance
“…One of the di culties with bene t incidence analyses is obtaining the cost of services. In the absence of the cost of services, the modal value of OOP payment for delivery has been used in the literature [53]. For our study we used the median value rather than the mean and mode of OOP as a proxy for the cost of services.…”
Section: Bene T Incidence Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…One of the di culties with bene t incidence analyses is obtaining the cost of services. In the absence of the cost of services, the modal value of OOP payment for delivery has been used in the literature [53]. For our study we used the median value rather than the mean and mode of OOP as a proxy for the cost of services.…”
Section: Bene T Incidence Analysismentioning
confidence: 99%
“…In Northeast India, the bene ts of inpatient care were pro-poor in urban and pro rich in rural areas [52]. A recent study found a pro-rich distribution of public subsidy for inpatient care of non-communicable diseases (NCDs) among the elderly [53]. In West Bengal, the bene t of public subsidy was highest for the lower-middle income group in rural areas and for the upper-middle income group in urban areas [23].…”
Section: Introductionmentioning
confidence: 99%
“…In Northeast India, the benefits of inpatient care were pro-poor in urban and pro rich in rural areas [52]. A recent study found a prorich distribution of public subsidy for inpatient care of non-communicable diseases (NCDs) among the elderly [53]. In West Bengal, the benefit of public subsidy was highest for the lower-middle income group in rural areas and for the upper-middle income group in urban areas [23].…”
Section: Introductionmentioning
confidence: 99%
“…One of the di culties in bene t incidence analyses is obtaining the cost of services. In the absence of cost of services, the modal value of OOP payment for delivery has been used in literature [43]. However, we have used the median value in our study since a signi cant proportion of women reported zero OOP (varying from 7-10% across the wealth quintile) of delivery at the accredited private health centres (JSY under NHM programme has such provision) and so the modal value for OOP payments became zero.…”
Section: Bene T Incidence Analysismentioning
confidence: 99%
“…In Northeast India, the bene ts for inpatient care in urban area were pro-poor whereas for rural areas, the bene ts were pro-rich in nature [42]. A recent study found a pro-rich distribution of public subsidy for inpatient care of non-communicable diseases (NCDs) among elderly [43]. In West Bengal, the bene t of public subsidy was highest for individuals belonging to lower-middle group in rural areas and upper-middle income group in urban areas [44].…”
Section: Introductionmentioning
confidence: 99%